Long-Term Results of Hybrid Left Ventricular Reconstruction in the Treatment of Ischemic Cardiomyopathy - Naar, Jan; Skalský, Ivo; Krűger, Andreas; Málek, Filip; Van Bladel, Kevin; Annest, Lon S; Moučka, Petr; Mráz, Tomáš; Reddy, Vivek Y; Neužil, Petr (Journal of cardiovascular translational research, 2021)
The evidence supporting surgical aneurysmectomy in ischemic heart failure is inconsistent. The aim of the study was to describe long-term effect of minimally invasive hybrid transcatheter and minithoracotomy left ventricular (LV) reconstruction in patients with ischemic cardiomyopathy. Twenty-three subjects with transmural anterior wall scarring, LV ejection fraction 15-45%, and New York Heart Association class ≥ II were intervened using Revivent TC anchoring system. LV end-systolic volume index was reduced from 73.2 ± 27 ml at baseline to 51.5 ± 22 ml after 6 months (p < 0.001), 49.9 ± 20 ml after 2 years (p < 0.001), and 56.1 ± 16 ml after 5 years (p = 0.047). NYHA class improved significantly at 5 years compared to baseline. Six-min walk test distance increased at 2 years compared to the 6-month visit. Hybrid LV reconstruction using the anchoring system provides significant and durable LV volume reduction during 5-year follow-up in preselected patients with ischemic heart failure. Legend: Hybrid left ventricular reconstruction using the anchoring system provides significant and durable LV volume reduction throughout 5-year follow-up in preselected patients with ischemic heart failure.
Keywords: Walk Test; Left ventricular aneurysm; kardiomyopatie; Stroke Volume; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; Ischemic cardiomyopathy; Middle Aged; mužské pohlaví; Myocardial Ischemia; Cardiac Surgical Procedures; Prospective Studies; Left ventricular reconstruction; tepový objem; Hybrid approach; ženské pohlaví; test chůzí; Humans; kardiochirurgické výkony; prospektivní studie; Cardiomyopathies; lidé středního věku; ischemická choroba srdeční; zákroky plastické chirurgie; Female; Plastic Surgery Procedures; lidé; Male